2015
DOI: 10.1515/intag-2015-0035
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble polysaccharides from Opuntia stricta Haw. fruit peels: recovery, identification and evaluation of their antioxidant activities

Abstract: A b s t r a c t. Opuntia stricta Haw. is considered as one of the most common cactus plant growing in Tunisia. Extracting valuable compounds from its fruit peel, considered as by-product, is drawing more and more attention, making it on the verge of commercialization. Water-soluble polysaccharides were extracted from Opuntia stricta Haw. peels, and their chemical composition assessed using thin layer chromatography. The antioxidant activities of the extracted polysaccharides were assessed using 2,2-diphenyl-1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 44 publications
5
16
0
1
Order By: Relevance
“…Soluble flaxseed gum (SFG) were extracted from hulls as previously described [ 26 ]. In brief, 20 g of hulls was mixed with 500 mL distilled water in a 1 L rounded bottom flask.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soluble flaxseed gum (SFG) were extracted from hulls as previously described [ 26 ]. In brief, 20 g of hulls was mixed with 500 mL distilled water in a 1 L rounded bottom flask.…”
Section: Methodsmentioning
confidence: 99%
“…Investigating other health-related benefits of SFG—such as its antioxidant potential, which has not been described before—is interesting, as it may lead to the replacement of some synthetic antioxidants, which are more and more restricted by legislation [ 25 ]. In fact, water-soluble polysaccharides extracted from plant materials and by-products may exhibit antioxidant activities, such as those extracted from red prickly pear peels [ 26 ], almond gum [ 27 ], garlic straw [ 28 ], almond and pistachio juice processing by-products [ 29 ], and many other examples. In this line, this work aims at extracting SFG from hulls and evaluating its antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%
“…Fruit peel has proved to be relevant as a source of nutraceuticals in the diet of humans or animals. Thus, the peels of banana (AGAMA-ACEVEDO et al, 2016), mango (JAHURUL et al, 2015, opuntia (KOUBAA et al, 2015), rambutan (WANLAPA et al 2015), passion fruit (JANEBRO et al, 2008;KULKARNI;VIJAYANAND, 2010) among others, have been utilized. In this study, we have found that in general the pulp holds more nutrients, with higher contents of K and Fe (4.3 and 42.5 µg/100 g) ( Table 3).…”
mentioning
confidence: 99%
“…It also differs from WSP obtained from O. monacantha which had rhamnose, arabinose, and glucose as the main sugar (Zhao, Yang, Yang, Jiang, & Zhang, 2007) and O. stricta which had rhamnose and galactose as the main sugars (Koubaa et al, 2015). The WSP of O.…”
Section: Discussionmentioning
confidence: 58%
“…This differs from the WSP isolated from Opuntia dillenii which had a molecular weight of 6,479.1 kDa and consisted of rhamnose and glucose as their main sugars (Gao et al, ). It also differs from WSP obtained from O. monacantha which had rhamnose, arabinose, and glucose as the main sugar (Zhao, Yang, Yang, Jiang, & Zhang, ) and O. stricta which had rhamnose and galactose as the main sugars (Koubaa et al, ). The WSP of O. humifusa also contained uronic acid in a significant amount and small amount of proteins possibly present as impurities.…”
Section: Discussionmentioning
confidence: 79%